The challenges of an effective management control system in Fourth Industrial Revolution - Norhidayah, Mohamad (2017)
More than 800 students and staff from Faculty of Industrial Management attended public lecture program by Deputy Vice Chancellor (Student Affairs & Alumni) Prof. Dato’ Dr. Yuserrie Zainuddin. This event was organized by Faculty of Industrial Management and Office of Academic & International aiming to give an insight on the Fourth Industrial Revolution (Industry 4.0).